Designing an e-Learning Environment based on Computer Simulation and its Effectiveness on Developing some Official Skills and Improving Deep Learning Skills among Commercial Secondary Schools’ Students - Abdelaziz, Hamdi (Jordan Journal of Educational Sciences, 2013)
The purpose of this research was to design an e-Learning environment based on computer simulation and measure its effectiveness on developing some official skills and deep learning skills among commercial secondary schools’ students. To achieve this objective, the researcher conducted an experimental study on a sample consisting of (62) students from commercial secondary schools. To measure the office equipments operating, usage and maintenance skills, an observation check list consist of (25) items reflects that the operating, usage and maintenance skills has been developed A deep learning scale consists of (52) items was also used to assess the students’ degree of deep learning in executive secretary course. After applying computer-based simulation, there were significant differences between the experimental and the control group on official skills and deep learning skills. These differences were in favor of the experimental group. Based on these results, a set of educational recommendations are mentioned to generalize the usages of computer-based simulation in all practical courses and majors in vocational education.